Intention to Adopt Islamic Quality Standard: A Study of Hotels in Peninsular Malaysia - Ahmad, Rozila; Zainol, Noor Azimin; Abu Karim, Mohd Hyrul (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2019)
Since 2010, Malaysia is among the first choice travel destination in the global Muslim travel market. To better serve the market, in 2013 Islamic Quality Standard for hotels (IQS) was introduced in Malaysia. However, many are skeptical about its feasibility. It is not clear whether hotels in Malaysia are keen to adopt this standard. Despite the ambiguity, a quantitative study to ascertain the intention to adopt IQS remains scarce. The purpose of this study is to investigate hotel manager’s intention to adopt IQS. A total of 355 questionnaires were distributed to hotel managers throughout Peninsular Malaysia. Based on 72 usable returned questionnaires, it was found that most of the hotel managers were undecided on whether to adopt IQS or not. The percentage of those who were positive about the intention to adopt IQS was only slightly higher than those who were negative about it. Furthermore, it is important to note that the finding is based on marginal response rate where the majority of respondents are Muslim.